Role of mesenchymal cells in enhancing cosmetic outcomes for autologous augmented fat transfers for facial rejuvenation and reconstructive surgery - Ansari Lari, Soroush; Zumot, Maya Salem; Nemrish, Salsabiel; Fredericks, Salim (Frontiers in Medicine, 2024)
In recent years, autologous fat transfer (AFT) has gained popularity for reconstructive and cosmetic procedures due to its minimally invasive nature and natural-looking results. However, limitations such as unpredictable fat resorption and safety concerns persist. To address these issues, researchers have explored incorporating adipose-derived stromal cells (ADSCs) into fat grafts. Enriching fat grafts with ADSCs, often through stromal vascular fraction (SVF), shows promise in regenerative medicine, though their effectiveness remains debated. Some studies suggest no significant difference in outcomes, while others indicate that ADSCs are more effective in larger-volume grafts. This implies that ADSC-enriched grafts might achieve similar results to traditional methods, with volume retention being a crucial success indicator. Given that these cosmetic procedures impact body image and self-confidence, innovative techniques like ADSC-enriched grafts are crucial for improving clinical outcomes. ADSCs are favoured for their abundance in adipose tissue and wound healing properties, which enhance cosmetic results. Patients receiving ADSC-enriched grafts show increased collagen, elastin, and CD31 levels, and better graft survival compared to those with traditional fat grafting, reducing the need for repeat procedures. Recent applications in patients with fibrotic facial deformities have demonstrated positive outcomes both cosmetically and psychologically. This mini-review evaluates the efficacy and benefits of ADSC-enriched AFT for facial rejuvenation and reconstruction, focusing on graft retention and overall procedural outcomes.